2018
DOI: 10.1182/bloodadvances.2018016048
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of MYC, a bona fide client of HSP90, contributes to intrinsic ibrutinib resistance in mantle cell lymphoma

Abstract: The BTK inhibitor ibrutinib has demonstrated a remarkable therapeutic effect in mantle cell lymphoma (MCL). However, approximately one-third of patients do not respond to the drug initially. To identify the mechanisms underlying primary ibrutinib resistance in MCL, we analyzed the transcriptome changes in ibrutinib-sensitive and ibrutinib-resistant cell lines on ibrutinib treatment. We found that MYC gene signature was suppressed by ibrutinib in sensitive but not resistant cell lines. We demonstrated that MYC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 51 publications
2
52
0
Order By: Relevance
“…Similar to CLL, IGHV mutation status and VH gene usage type is important in MCL, and mutated MCL patients have a better outcome compared to unmutated IGHV patients; however, the significance of IGHV mutation status in MCL is underestimated . Other factors with inferior outcomes include CDKN2A (locus 9p21) mutations, MYC overexpression, NOTCH1 and/or NOTCH2 mutations, NSD2 mutations ( NSD2 [ WHSC1 ] mutations are associated with an increase in H3K36 and a decrease in H3K27 methylation across the genome, thus promoting oncogenesis), CCND1 mutations, and elevated absolute monocyte count . Baculoviral IAP repeat containing three mutations ( BIRC3 ) are seen in 10%‐15% of patients with MCL .…”
Section: Advances In MCL Prognosticationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to CLL, IGHV mutation status and VH gene usage type is important in MCL, and mutated MCL patients have a better outcome compared to unmutated IGHV patients; however, the significance of IGHV mutation status in MCL is underestimated . Other factors with inferior outcomes include CDKN2A (locus 9p21) mutations, MYC overexpression, NOTCH1 and/or NOTCH2 mutations, NSD2 mutations ( NSD2 [ WHSC1 ] mutations are associated with an increase in H3K36 and a decrease in H3K27 methylation across the genome, thus promoting oncogenesis), CCND1 mutations, and elevated absolute monocyte count . Baculoviral IAP repeat containing three mutations ( BIRC3 ) are seen in 10%‐15% of patients with MCL .…”
Section: Advances In MCL Prognosticationmentioning
confidence: 99%
“…Overall, the advent of ibrutinib is a “great leap forward” in the treatment of MCL; however, problems with ibrutinib discontinuation, management of ibrutinib‐refractory disease, and mechanisms of ibrutinib resistance pose new challenges. In contrast with SLL/CLL, where the C481S mutation is commonly associated with ibrutinib resistance, this mutation is infrequent in ibrutinib‐resistant MCL, and other mechanisms of ibrutinib resistance and ways to overcome ibrutinib resistance must be explored. A detailed discussion about the molecular aspects of ibrutinib resistance is beyond the scope of the current article.…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 99%
“…MYC has first been reported to be a client protein of HSP90 in mouse fibroblasts [ 20 ]. More recently, the MYC-HSP90 axis has been shown to be important in a variety of cancers, including but not limited to, breast cancer stem cells and mantle cell lymphoma [ 13 , 21 ]. To determine if HSP90 physically interacts with MYC in Burkitt lymphoma, we performed co-immunoprecipitation (Co-IP).…”
Section: Resultsmentioning
confidence: 99%
“…These drugs competitively bind the N-terminal ATP site of HSP90, causing proteasomal degradation of HSP90-dependent client proteins [ 10 , 11 , 12 ]. Interestingly, MYC has been reported to be a client of HSP90 in mantle cell lymphoma [ 13 ], and inhibition of HSP90 function has been shown to cause destabilization of MYC and NMYC proteins in neuroblastoma, which was associated with decreased tumor cell proliferation, cell cycle arrest, increased apoptosis, and upregulation of tumor suppressors, such as p53 [ 14 ]. Furthermore, it has been shown that HSP90 protein expression is elevated in Burkitt lymphoma and may provide as a target for therapeutic intervention [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…17 MYC is a crucial client protein of HSP90 and the HSP90-MYC complex is important in cell cycle progression. 18 The drug Ganetespib (STA-9090) is a second-generation HSP90 inhibitor that presents potent cytotoxicity in a range of solid and hematological tumors and demonstrates antitumor activity with promising safety profiles in vivo in a variety of cancers. 19 At present, many Phase I-III clinical trials of STA-9090 for human cancer treatment are ongoing, including breast and lung cancers.…”
Section: Introductionmentioning
confidence: 99%